SISTEM PENDUKUNG KEPUTUSAN SELEKSI CALON PENERIMA BANTUAN PROGRAM KELUARGA HARAPAN (PKH) DENGAN METODE AHP DAN PROMETHEE ( STUDI KASUS PADA KELURAHAN KUDAILE SLAWI ) - Sri Anjarwati; Farahdibah Farahdibah (Jurnal Surya Informatika: Membangun Informasi dan Profesionalisme, 2017)
Program Keluarga Harapan (PKH) still poses a padaKantor kerancauan Kudaile village, because the selection process is still using the data in a couple of years ago. This causes PKH help does not reach the right targets. Therefore, this research aims to design and build a decision support system for selecting recipients PKH.Dalam help this Decision Support System methods used are a combination Analycal Hierarchy Process (AHP) Ranking dan Preference Organization for Enrichment Evaluation (Promethee). In practice, the first to get a run AHP criteria weight. After that, Promethee executed to determine perangkingan of the selection process. In this study, AHP combined with Promethee in order to obtain better results and recommendations for the selection of beneficiaries objective PKH help.